Assessment of leaf micromorphology after full desiccation of resurrection plants. (2nd January 2019) - Vassileva, Valya; Moyankova, Daniela; Dimitrova, Anna; Mladenov, Petko; Djilianov, Dimitar
Abstract: Resurrection plants are unique among higher plants because of their ability to withstand long periods of dehydration without damages. In this study, leaf epidermis and palisade mesophyll of three resurrection species, Haberlea rodopensis, Ramonda serbica and Ramonda myconi, grown under full desiccation and benign conditions, were analyzed by differential interference contrast microscopy. Detailed investigation of adaxial and abaxial leaf surfaces revealed species-specific differences in the size and number of epidermal cells and stomatal density. The applied full desiccation did not cause any significant deviations of these parameters from the controls. There were no changes in the size and number of mesophyll cells as well. Analysis of stomatal patterning displayed essentially hypostomatic leaves, having stomata mainly abaxially positioned. The most significant change detected in the leaves of dehydration-treated plants was the increased formation of adaxially positioned trichomes. This increase was very high in R. myconi, where the adaxial leaf surface was fully covered by trichomes. Despite the existence of small species-specific differences, the results showed uniform desiccation-related responses of the studied resurrection species. The quantified leaf epidermal and mesophyll features are discussed with respect to their possible contribution to the desiccation tolerance of resurrection species.